Recommended First-Line Antiretroviral Therapy Regimens and Risk of Diabetes Mellitus in HIV-Infected Adults in Resource-Limited Settings - Ninutcha Paengsai (2020)
© 2019 The Author(s) 2019. Published by Oxford University Press on behalf of Infectious Diseases Society of America. Objective: The use of some antiretroviral drugs has been associated with a higher risk of diabetes mellitus (DM) in HIV-infected patients, but the risk associated with antiretroviral drug combinations remains unclear. We investigated the association between first-line antiretroviral therapy (ART) regimens, recommended by the World Health Organization (WHO) in 2016, and the risk of DM in adults. Method: We selected all HIV-infected adults within the Thai National AIDS Program who started a first-line ART regimen consisting the following between October 2006 and September 2013: zidovudine+lamivudine+nevirapine; tenofovir disoproxil fumarate (TDF)+lamivudine+nevirapine; zidovudine+lamivudine+efavirenz; TDF+lamivudine/emtricitabine+efavirenz; zidovudine+lamivudine+ritonavir-boosted lopinavir (LPV/r); or TDF+lamivudine+LPV/r. Diagnosis of DM was defined as having at least 2 of the following characteristics: fasting plasma glucose ≥126 mg/dl, 2010 WHO ICD-10 codes E11-E14, or prescription of antidiabetic drugs. To identify ART regimens associated with DM, we used competing risks regression models that considered mortality without DM as a competing event and adjusted for sex, age, pancreas disease, and stratified by groups defined by a score summarizing the propensity to receive a specific first-line ART regimen. Results: Data from 35 710 adults (49.1% male; median age, 35.0 years; median follow-up, 2.0 years) were included. In the multivariable analysis with zidovudine+lamivudine+nevirapine as the reference group, a higher risk of DM was observed with TDF+lamivudine/emtricitabine+efavirenz (adjusted sub-distribution hazard ratio [aSHR], 1.6; 95% confidence interval [CI], 1.3-1.9), zidovudine+lamivudine+efavirenz (aSHR, 2.0; 95% CI, 1.7-2.3), and TDF+lamivudine+LPV/r (aSHR, 2.7; 95% CI, 1.9-3.9). Conclusions: Several of the WHO recommended ART regimens, particularly tenofovir + lamivudine +LPV/r and regimens containing efavirenz, may be associated with an increased risk of DM.